(untitled) (European Journal of Pure and Applied Mathematics, 2010)
In this paper,Â we determine the structure of nonlocal commutative ringsÂ with p^6 zero-divisors and characterize the structure of nonlocal commutative ringsÂ with p^7 zero-divisors. Also, the structure and classificationÂ up to isomorphismÂ all commutativeÂ rings withÂ p_1^k_1… p_n^k_nÂ zero-divisors, where n is aÂ positive integer,Â p_i^,s are distinct prime number and 1≤Â k_i≤ 4, are determined.